Riding the Storm : Fiscal Sustainability in the Caribbean - Cevik, Serhan (IMF Working Papers; Working Paper, 2020)
Fiscal sustainability remains a paramount challenge for small economies with high debt and greater vulnerability to climate change. This paper applies the model-based sustainability test for fiscal policy in a panel of 16 Caribbean countries during the period 1980-2018. The results indicate that the coefficient on lagged government debt is positive and statistically significant, implying that fiscal policy in the Caribbean takes corrective actions to counteract an increase in the debt-to-GDP ratio. Nonlinear estimations, however, show that the quadratic debt parameter is negative, which indicates that fiscal policy response is not adequate to ensure sustainability at higher levels of debt. We also find that the fiscal stance tends to be countercyclical on average during the sample period. These empirical results confirm that maintaining prudent fiscal policies and implementing growth-enhancing structural reforms are necessary to build fiscal buffers and ensure debt sustainability with high probability even when negative shocks occur over the long term.